Migration and pastoral power through life course: Evidence from Georgia. Issue 91 (May 2018) - Bailey, Adrian J.; Drbohlav, Dusan; Salukvadze, Joseph
Highlights: Pastoral power flows through life course. Prayer, biographical management and family remitting are key tests of truth. Diverse governmentalities invoke and work through life course. The gendering of Georgian migration is linked to life course. Abstract: This article advances critical migration theory by exploring how pastoral power works through relational life courses. Extending governmentality accounts, we posit and trace the circulation of use, exchange, and surplus values across the life courses of migrants from the former Soviet republic of Georgia. Field evidence shows how practices of migration, remitting, and familyhood are associated with dependent social relations and concealment, and negotiated through tests of truth of prayer, biographical management, and family remitting. This conduct of everyday life simultaneously invokes life courses as registers of resources and possibilities and subjects of the multiple governmentalities associated with recent discourse and European and Georgian migration policy initiatives, including "Safe Migration" and migration management systems. We conclude that studying how pastoral power works through relational life courses expands understanding of migration and, in the case of Georgia, highlights the importance of gender, family, and religious organisations for contemporary migration issues.